The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.1002/asia.202101289
|View full text |Cite
|
Sign up to set email alerts
|

Encapsulation of Metal Clusters within Porous Organic Materials: From Synthesis to Catalysis Applications

Abstract: Metal clusters (MCs) with dimensions between a single metal atom and nanoparticles of >2 nm usually possess distinct geometric and electronic structures, and their outstanding performance in catalysis applications have underpinned a broad research interest. However, smaller‐sized MCs are easily deactivated by migration coalescence during the catalysis process because of their high surface energy. Therefore, the search of an appropriate stabilizer for MCs is urgently demanded. In recent years, porous organic po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 101 publications
0
8
0
Order By: Relevance
“…Among the reported porous matrixes, organic molecular cages, as newly developed microporous materials, have attracted increasing attention over the past few years . Such materials are composed of discrete molecules with intrinsic, guest-accessible cavities, which can be used to confine the MNPs and prevent aggregation. Recently, the use of size-adjustable cavities of different kinds of organic cages to modulate MNP size and related catalytic activity has experienced rapid development. Although great progress has been made, it remains a great challenge to compromise encapsulation and mass transfer in catalytic processes. In particular, the nanosized discrete pore once encapsulating the MNPs may block accessibility to some extent, which is detrimental to mass transfer, especially in the case of catalysis involving substrates of different sizes/geometries.…”
Section: Introductionmentioning
confidence: 99%
“…Among the reported porous matrixes, organic molecular cages, as newly developed microporous materials, have attracted increasing attention over the past few years . Such materials are composed of discrete molecules with intrinsic, guest-accessible cavities, which can be used to confine the MNPs and prevent aggregation. Recently, the use of size-adjustable cavities of different kinds of organic cages to modulate MNP size and related catalytic activity has experienced rapid development. Although great progress has been made, it remains a great challenge to compromise encapsulation and mass transfer in catalytic processes. In particular, the nanosized discrete pore once encapsulating the MNPs may block accessibility to some extent, which is detrimental to mass transfer, especially in the case of catalysis involving substrates of different sizes/geometries.…”
Section: Introductionmentioning
confidence: 99%
“…Functional organic materials retain their leading position in the evolution of chemistry and materials science. [1][2][3][4] Various organic compounds with different physicochemical properties and especially those bearing different states of aggregation are considered as promising functional materials. Recent investigations in this research area revealed that the incorporation of a nitrogen heteroaromatic motif into the molecular structure provides a substantial improvement of the materials' properties and broadens their application potential in comparison with the respective carbocyclic analogues.…”
Section: Introductionmentioning
confidence: 99%
“…Organic materials constitute an important and enormous class of chemical substances with a wide set of practical applications in various areas of materials science. Structurally diverse organic compounds with different physicochemical properties are considered promising functional materials. Keeping in mind a constant search for the “ideal” material with a desired set of functional properties, leading research groups focused their attention on the utilization of aromatic nitrogen heterocycles as a suitable platform for the design of next-generation organic materials. This trend remains absolutely relevant in the creation of novel high-energy materials possessing balanced physicochemical and detonation properties. …”
Section: Introductionmentioning
confidence: 99%